Interpretación geométrica de algunas variedades de Schubert - Escamilla, Juan F. (1997)
In this article we give some geometrical interpretations of the Schubert-varieties of the Grassmannians G(2,4), G(3,5) and G(2,5), and some of their applications to enumerative geometry.